PERBANDINGAN ALGORITMA BRANCH AND BOUND DAN ALGORITMA GENETIKA UNTUK MENGATASI TRAVELLING SALESMAN PROBLEM (TSP) (Studi Kasus PT. JNE Semarang) - Nugroho, Ari Yulianto; Suyitno, Amin; Arifudin, Riza (Universitas Negeri Semarang, 2016)
This study examines an optimum solution to the search of Travelling Salesman Problem (TSP). The purpose of this paper is finding the shortest route at PT. Jalur Nugraha Ekakurir (JNE) Semarang on condition that every town is just visited once, except for the beginning address. Branch and bound algorithm dan genetic algorithm, is proposed to solve optimization problems with using Matlab software. Measurement of the effectiveness of the work system is done by comparing the calculation results between the branch and bound algorithm and genetic algorithm which is the best modification. Population size, pc, pm, and the number of generations are used as modifications. The results showed that the length of the resulting circuit using genetic algorithm is smaller than the length of using circuit branch and bound algorithm. This shows that genetic algorithm is more effective in determining the shortest circuit for delivery of goods in PT. Jalur Nugraha Ekakurir (JNE) Semarang